Análises físico-químicas, microbiológicas e sensoriais de leites fermentados com potencial probiótico adicionados de farinhas integrais de sorgo irradiadas. - Danielle Fatima D' Angelis (2020)
The search for healthy foods, which in addition to nourishing has functional resources, has become increasingly greater over the years, boosting the developing new products, especially with the addition of probiotics, with emphasis on those with a dairy base, such as yogurts and fermented milks that they are rich in nutrients and widely consumed by the population. The incorporation of cereals in these types of foods has been studied, as it contributes to increase fiber consumption, in addition to enriching it with bioactive compounds, which exhibit antioxidant properties. The objective of this study was to evaluate the influence of the treatment by low dosage irradiation in quality of integral sorghum flours (FIS) of the genotypes BR 501 (without tannin) and BRS 305 (with tannin), as well as selecting the best flours for application in milk potentially probiotic fermentation (Streptococcus thermophillus, Lactobacillus bulgaricus and Lactobacillus acidophilus La-5). The FIS were irradiates at dosages of 0 kGy (control), 3 kGy and 5 kGy and was subjected to microbiological analysis of molds and yeasts, total and fecal coliforms (NMP method), Bacillus cereus and the presence of Salmonella sp., as well as indication of pH, acidity, water activity, centesimal composition, instrumental color, concentration of bioactive compounds, antioxidant activity and technological properties. The FIS radiated with 5 kGy, both genotypes were subjected to an analysis of resistant starch concentration and granulometry, being selected for the development of five formulations of fermented milk with probiotic potential (L. acidophilus La-5), control: without FIS; 1% BR 501: added 1% of the FIS BR 501; 2% of BR 501: added to 2% of FIS BR 501; 1% BRS 305: added 1% of FIS BRS 305 and 2% BRS 305: added 2% of FIS BRS 305. The formulations submitted to sanitary hygienic quality analysis, centesimal composition, instrumental color and texture, concentration of bioactive compounds, activity antioxidant (ABTS method), and sensory acceptance/purchase intention (with one hundred and ten evaluators), in addition to monitoring pH, acidity and viability of L. acidophilus La-5 during 28 days of storage under refrigeration. In the microbiological analysis, there was an absence of Salmonella sp. and values below the limit of detection of methods for total and fecal coliforms in all flours, and samples such as applied irradiation dosages (3 kGy and 5 kGy), eliminating the presence of molds and yeasts and suggested colonies of Bacillus cereus found in the culture medium Agar Mannitol Egg Yolk Polymyxin (MYP) in the samples controls. There were changes in color with darkening in the two genotypes of FIS irradiated, with no significant difference between irradiation dosages. In all the FIS there were no significant changes in the centesimal composition, in the concentration of phenolic compounds, tannins and anthocyanins, in the antioxidant activity and in the technological methods of the absorption indices: water, oil and milk and water solubility index. FIS of the irradiated BRS 305 genotype (5 kGy) stood out with a higher content of resistant starch and less granulometry. Fermented milks with probiotic potential were obtained because they contain adequate amounts of Lactobacillus acidophilus La-5 during storage with pH stability and acidity for 28 days. The irradiation process at low dosages proved to be efficient in the treatment of FIS, with emphasis on the dosage of 5 kGy, which eliminated all the initial microbial load present, without causing changes in nutritional quality. The addition of FIS of the BR 501 and BRS 305 genotypes irradiated, contributions to the increase in the textural cohesiveness parameter, and without increasing the concentration of bioactive compounds and antioxidant activity and maintaining the viability of L. acidophilus La-5 and over 28 days, with emphasis on formulations 1% BRS 305 and 2% BRS 305 that present good sensory acceptance and purchase intention by the evaluators, that open perspectives for the insertion of sorghum with tannin in human food. In general, the present study allowed the development of food products with functional potential, being good options to meet the market demand focused on the consumption of healthy foods and that bring health benefits.